Change in Serum Cystatin C Level as Predictor for Length of Hospital Stay in Patients Undergoing Primary Percutaneous Coronary Intervention - Putra, Andika; Prasanto, Raden Heru; Puspitasari, Metalia (Acta Interna The Journal of Internal Medicine, 2023)
Background. Percutaneous Coronary Intervention (PCI) is one of the most frequently performed medical procedures. Length of stay for patients after undergoing PCI should be standardized to achieve the best quality of health services. The existence of complications is one of the main factors considering the length of stay after PCI. Cystatin C has the ability as a predictor of complications in patients with acute coronary syndrome, especially those undergoing PCI, as well as the increase in length of stay associated with complications after the PCI procedure.Objectives. To determine the average changes in serum cystatin C levels, the correlation between serum cystatin C levels and length of treatment, and changes in serum cystatin C levels as predictors of length of stay in patients undergoing primary PCI at Dr. Sardjito Hospital.Methods. Analytical observational study with a prospective cohort method conducted on patients with a STEMI diagnosis who underwent primary PCI procedures in Emergency Room, Cardiovascular Care Unit (CVCU) of Dr. Sardjito Hospital, treated from November 2020 to April 2021. The data was then analyzed for normality, multicollinearity, bivariate, and multivariate tests to see the effect of changes in cystatin C and other variables on the length of stay for patients after primary PCI (p <0.05 is significant).Results. Of the 111 patients, 92 patients were subjected to further analysis. Patients included in the study had an average age of 59.55 (+10.80) years, majority of men, reduced LVEF, using trans-radial PCI access, Killip I, average eGFR of 64 ml / 1.73m2, length of stay in hospital is 5 days, delta cystatin C and creatinine 0.10 and 0.04 U / L, respectively. The increase in cystatin C had a moderate positive correlation (0.502) with the length of hospital stay (p<0.001), in multivariate analysis serum cystatin C does not correlate with length of hospital stay (p=0.590). Other variables including LVEF, eGFR, infection, and contrast-induced acute kidney injury had a significant correlation with length of stay (p<0.001). The multivariate test showed that LVEF, eGFR, and infection had the most significant correlation (p = 0.034; 0.001; 0.005 respectively) to the length of hospital stay with a regression coefficient of 0.72; -0.04; and 1.93.Conclusion. An increase of cystatin C serum does not correlate significantly with the length of hospitalization in STEMI patients undergoing PCI procedure in Dr. Sardjito Hospital.